Remote management: traditional leadership behaviors in a contemporary work environment - Watson, Kelley D (Kansas State University, 2007)
Today the geographic distance between workers is increasing. The purpose of this study was to investigate the distributed work environment by specifically focusing on leader behavior and its impact on subordinate outcomes. This study asked if the traditional core set of leadership behaviors is effective in distributed work environments, and how those behaviors impact employee outcomes such as commitment and satisfaction with supervision. Several fundamental and explored questions included: Do essential management behaviors such as consideration and initiating structure materialize differently in face-to-face versus remote situations, what type of leadership will have the most positive impact on employee's perceptions of satisfaction with supervision and organizational commitment, and does this differ according to the amount of face time between the manager and employee? Correlational data results did not support the hypotheses that face to face interaction scores were positively correlated with affective commitment, or satisfaction with supervision. Face to face interaction was not negatively correlated with continuance commitment. Non-remote employees reported significantly higher levels of satisfaction with supervision than remote employees. There was a significant difference between remote and non remote employees with non remote employees reporting higher levels of career advancement than remote employees. There was a stronger relationship between initiating structure and satisfaction with supervision when spatial distance was high. It appears that spatial distance acted as an enhancer. Two scales, company support for remote management and remote management specific behaviors, were analyzed to obtain preliminary data for future research.
Keywords: Remote leadership; Remote management; E-leadership; Distributed teams; Virtual leadership; Spatial distance; Psychology, Industrial (0624)